2015
DOI: 10.1177/2374373515615977
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Inpatient Experience Survey Items and Domains With Overall Hospital Rating

Abstract: Objective:To determine which individual patient experience questions and domains were most correlated with overall inpatient hospital experience.Methods:Within 42 days of discharge, 27 639 patients completed a telephone survey based upon the Hospital-Consumer Assessment of Healthcare Systems and Processes instrument. Patients rated their overall experience on a scale of 0 (worst care) to 10 (best care). Correlation coefficients were calculated to assess the relationships between individual survey questions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
1
15
1
1
Order By: Relevance
“…The physical design of the health‐care environment influences patient safety (reducing errors, patient falls, infections, etc.) and patient experience (supporting privacy and comfort) . Further, environments should integrate services to accommodate patients, such as language support and, appropriate and flexible visiting hours .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physical design of the health‐care environment influences patient safety (reducing errors, patient falls, infections, etc.) and patient experience (supporting privacy and comfort) . Further, environments should integrate services to accommodate patients, such as language support and, appropriate and flexible visiting hours .…”
Section: Discussionmentioning
confidence: 99%
“…), which measure patient health status, quality of life and symptoms, functionality, physical, mental or social health; Patient Reported Experience Measures (PREMs; O2b.) measure patient experiences with the health‐care system; and Patient‐Reported Adverse Outcomes (PRAOS; O2c.) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified that the provider’s performance in the humanistic care domain has the largest positive effect on the overall rating of the patient experience in both the ambulatory care and hospitalisation setting and across all hospital categories. However, Kemp et al found that communication with nurses has the strongest correlation with the overall inpatient experience based on the HCAHPS survey in the Canadian context 37. Aaronson et al reported that communication mattered most for the overall emergency department rating in a retrospective cohort study in America 38.…”
Section: Discussionmentioning
confidence: 99%
“…This study used binary logistic regression and controlled for age, gender, race, education, preferred language, and self-reported health status of randomly sampled subjects ( N = 136,546) and had an overall average response rate of 34%. More recently, a Canadian study that utilized the HCAHPS survey items with 27,492 discharged, English-speaking patients over a 3-year period found that of all the HCAHPS factors, the nurse communication factor had the strongest Pearson correlation with overall experience ratings ( r = .45, p < .001) (Kemp, McCormack, Chan, Santana, & Quan, 2015). Additionally, it was found that the factors of pain management, room cleanliness, and room quietness were also significantly related to overall experience ratings ( r = .31 to .42, p <.001).…”
Section: Related Literaturementioning
confidence: 99%